Design and Optimization of Targeted Nanoparticles for Delivery of Quercetin from Allium Cepa for Treatment of Colorectal Cancer - Chopde, Nitin; Manoj Rewatkar, Rasika; M Chavan, Ghanshyam; S. Subathra, S. Subathra; Devi, Ritismita; Hari V, Hari V; Uttekar, Pravin S.; Rathore, Shruti; Sura, Syam Prasad (Journal of Neonatal Surgery, 2025)
Introduction: The development of effective and tailored therapy options is crucial, as colorectal cancer (CRC) continues to be a top cause of cancer-related mortality globally. The flavonoid quercetin has strong anticancer effects but is quickly metabolized and has low bioavailability. It is derived from the onion plant Allium cepa. In order to improve the treatment effectiveness against CRC while reducing systemic toxicity, this work seeks to develop and optimize tailored nanoparticles for quercetin delivery. Materials and Methods: Solvent evaporation was used to formulate quercetin-loaded nanoparticles (NPs) utilizing poly(lactic-co-glycolic acid) (PLGA) as the polymeric matrix. The formulation parameters that were optimized using a Box-Behnken design were the concentration of polymer (50-150 mg), the concentration of surfactant (0.5-1.5% w/v), and the stirring speed (5000-15000 rpm). The response variables included particle size, entrapment efficiency, and drug release. In order to actively target CRC cells that overexpress folate receptors, the nanoparticles were surface-functionalized with folic acid. Drug loading, in vitro drug release, surface morphology, zeta potential, particle size analysis (DLS), and PBS (pH 7.4) were all part of the characterization process. Researchers used HT-29 colorectal cancer cells to study cytotoxicity and cellular uptake; flow cytometry was used to evaluate apoptosis. Results: The optimized nanoparticles demonstrated a sustained drug release profile for 48 hours, an entrapment efficiency of 87.6 ± 3.2%, and a particle size of 165.4 ± 5.8 nm. Conjugation of folic acid into NPs increased cellular absorption 2.5-fold over non-targeted NPs. The IC₅₀ value of 18.2 µM for targeted NPs was found to be much lower than that of free quercetin (42.5 µM), suggesting that the therapeutic efficacy was increased, according to cytotoxicity studies. Compared to free quercetin, which had a cell death rate of 29.4 percent, apoptosis research showed that treated CRC cells had a cell death rate of 63.7 percent. Conclusion: Enhanced cytotoxicity, effective targeted delivery, and apoptotic induction in CRC cells were all shown by the optimized nanoparticles loaded with quercetin. The use of this tailored nanocarrier system to enhance quercetin's therapeutic potential in the treatment of colorectal cancer is an encouraging development. These results need to be confirmed by more in vivo investigations.